Impact of Mui Halal Labels on Volume of Sales of Holland Bakery in Manado City - Mawarni Safitri Henaulu (Tasharruf: Journal Economics and Business of Islam, 2019)
AbstractThis research examines the impact of MUI's halal label on the sales volume of Holland bakery in the city of Manado. The main problem in this study is how much influence the halal label has on sales volume. The objective achieved in this study was to find out the impact of MUI's halal label on Holland Bakery's sales volume in the city of Manado. And provide recommendations to other food companies so that they can increase sales volume. This type of research is quantitative research. Data used in the study are primary data or data directly from respondents through questionnaires that are distributed in Holland Bakery in the city of Manado. As a population and a sample of consumers are Holland Bakery in the city of Manado. The data analysis technique used in this study is the normality test, hypothesis testing using product moment correlation test and simple linear regression test. After going through quantitative procedures.This study found that the halal label has an effect on sales volume as evidenced by the product moment correlation test. It is known that the correlation value between variables X and Y is 0.562> 0. So Ho is rejected and Ha is accepted. from the Model Summary table is 0.315 or around 31.5%. This means that the effect of the independent variable (Halal Label) on the dependent variable (Sales Volume) is 31.5%. Meanwhile, the remaining 68.5% (100-31.5 = 68.5%) are explained by other variables not examined in this study. Keywords: Halal Label, Sales Volume, Holland Bakery